Determinants of Transfer Pricing Aggressiveness with the Moderation of Corporate Governance in Indonesia and Malaysia - Dimas Eko Wahyudi; Sutrisno T; Mohammad Khoiru Rusydi (Universitas Hayam Wuruk Perbanas, 2021)
This research aims to analyze and empirically prove the effects of firm size, profitability, and leverage on transfer pricing aggressiveness moderated by corporate governance. It used a sample consisting of 73 multinational firms listed in both www.idx.co.id and www.bursamalaysia.com from 2018 to 2019. The data were analyzed using multiple linier regression and moderated regression analysis (MRA) to analyze and empirically prove the effects of firm size, profitability, and leverage on transfer pricing aggressiveness moderated by corporate governance. The results showed that leverage positively affected transfer pricing aggressiveness, whereas firm size and profitability did not. Corporate governance evidently weakened the effect of leverage on transfer pricing aggressiveness. This research contributes to increasingthe state revenue through the taxation sector by exposing the determinants of transfer pricing aggressiveness that harm the state, and to assist public policy makers, especially those who are in charge of the policies related to transactions with special relationship.